Thermodynamic Parameters and Interfacial Properties of Poly(ethylene glycol)‐octyl Sulfosuccinates. Issue 5 (28th March 2021) - Cai, Hongyan; Luo, Wenli; Zheng, Yancheng; Zhang, Yi; Lai, Lu; Tang, Shanfa
Abstract: Surface tension of a series of poly(ethylene glycol)‐octyl sulfosuccinates at different temperatures was measured, and the interfacial properties were investigated in the absence and presence of inorganic salts. Surface tension results indicate that critical micelle concentration (CMC) values of five surfactants (C8‐PEG200, C8‐PEG400, C8‐PEG600, C8‐PEG800, and C8‐PEG1000) decrease as the molecular weight of polyethylene glycol (PEG) segments and the experimental temperature increases. The surface activity of the C8‐PEG series changes with temperature, and the surface tension at the CMC ( γ CMC ) of the C8‐PEG series decreases initially and then increases as the PEG molecular weight increases. This behavior may be attributed to the dehydration of the surfactant molecules, resulting in the change of hydrophile–lipophile balance for the different EO numbers in the surfactant molecules, which form a different surface energy film at the air–water interface. Negative ΔGm indicates that the micellization process of these surfactants is spontaneous and an entropically driven process. For the water/alkane interface, these surfactants have low interfacial activity. The interfacial tension (IFT) between these surfactants and alkanes increases first and then decreases with the increase in the molecular weight of PEG segments. After the addition of salt, the interfacial activity of the investigated surfactants increases significantly. The IFT between C8‐PEG800 and 10–12 alkanes and between C8‐PEG1000 and 12–16 alkanes reaches a low IFT magnitude of 10 −2 mN m −1 in the presence of 0.5% CaCl2 or the mixed inorganic salts 0.5% NaCl+0.5% CaCl2 .